Problems of Using the Poetic Corpus of Abay For Pedagogical Purposes and Ways to Solve It - G.B, Madiyeva; K.K, Pirmanova; A.D, Serikbayeva; N.М Nurlybayev; D.O., Tokmyrzaev; A.Т Nagiyeva; Z.S, Yegizbayeva (Journal of Ecohumanism, 2025)
The use of the Abai poetic corpus for pedagogical purposes represents a unique opportunity to deepen students’ knowledge of Kazakh literature, culture, and history. However, the introduction of this tool into the educational process faces a number of challenges that limit its potential. This article examines the main difficulties associated with the use of the corpus, including the lack of information awareness among teachers, the shortage of teaching materials, and the low level of technical training of teachers. Attention is also paid to pedagogical skepticism and the lack of time to master innovative methods. An important part of the study is the proposed solutions to these problems. Among them are the development of educational programs for teachers, the creation of adapted materials based on the poetic corpus, and the provision of technical and methodological support to schools. The author emphasizes the importance of integrating Abai’s poetic heritage into school education as a means of forming national identity and developing students’ analytical skills. This work is addressed to teachers, methodologists, and education specialists interested in using modern teaching tools.